2019
DOI: 10.1016/j.celrep.2019.09.059
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism Linking Two Known Vulnerability Factors for Alcohol Abuse: Heightened Alcohol Stimulation and Low Striatal Dopamine D2 Receptors

Abstract: Graphical AbstractHighlights d Heightened ethanol stimulation has predictive value for ethanol abuse d Low D2 receptors on striatal projection neurons heightens ethanol stimulation d D2 receptors are linked to ethanol preference and drinking, despite adverse outcomes d Enhanced D1 receptor signaling is a key mechanism underlying abuse liability SUMMARY Alcohol produces both stimulant and sedative effects in humans and rodents. In humans, alcohol abuse disorder is associated with a higher stimulant and lower se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…In two previous studies, we showed that compulsive-like alcohol drinking in mice is associated with changes in Lrrk2 gene expression in the striatum ( 9 ) and that mice with enhanced D1R function display higher stimulation and preference for alcohol ( 37 ). Here we postulated that potentiation of D1R function by deletion of Lrrk2 from D1-MSN affects alcohol-related behaviors mediated by D1R.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In two previous studies, we showed that compulsive-like alcohol drinking in mice is associated with changes in Lrrk2 gene expression in the striatum ( 9 ) and that mice with enhanced D1R function display higher stimulation and preference for alcohol ( 37 ). Here we postulated that potentiation of D1R function by deletion of Lrrk2 from D1-MSN affects alcohol-related behaviors mediated by D1R.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we recently showed that mice that drink high levels of alcohol are more sensitive to the stimulatory effects of alcohol compared to low drinkers ( 37 ). Both alcohol-induced stimulation and alcohol drinking required activation of D1R in the dorsomedial striatum ( 23, 37, 62, 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general procedure involves mice drinking in one of these models for a set amount of time, and then having their alcohol solution adulterated with quinine with concentrations varying from 100 to 1,000 μM, though most commonly 100 to 250 μM has been used. This has primarily been done in male mice with no investigation into sex differences, though more recently female mice have been included in QuA experiments (Bocarsly et al, 2019; Houck et al, 2019; Sneddon et al, 2020) with some directly testing sex difference hypotheses (Sneddon et al, 2019; Top of Form Fulenwider, et al, 2019; Shaw et al, 2020). Compulsive‐like QuA drinking is then determined by the definition wherein compulsive mice will consume the same amount of QuA as nonadulterated alcohol, whereas noncompulsive mice would consume significantly less QuA than nonadulterated alcohol.…”
Section: References Quinine Concentration (μM) Alcohol History and Comentioning
confidence: 99%
“…Recent work, however, suggests that chronic alcohol exposure disrupts the balance between D1 and D2 signaling pathways in MSNs of the striatum leading to a more robust behavioral response to ethanol and resiliency to sedation. 55 D1 dopamine GPCRs in AUD. There are 2 human D1 receptors (DRD1 and DRD5).…”
Section: Dopaminergic Receptors In Audmentioning
confidence: 99%